2015
DOI: 10.1007/s00268-015-3117-2
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Pheochromocytomas in MEN2A Syndrome: A Two‐Institution Experience

Abstract: The accumulative risk of bilateral PHEOs almost reached 100 % but its onset was significantly earlier in C634R mutation. These findings implied that those with C634R mutation might benefit from earlier screening of contralateral PHEO than other C634 mutations after an unilateral adrenalectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…The D631Y germline mutation in MEN2 have also been reported in Germany [13,23], the Netherlands [24], and Turkey [25] but they were excluded from this analysis because results of thyroidectomy and family screening were not provided. We found that PCC occurred in 58.8% and MTC in 32.3% of the RET D631Y variant MEN2 patients, and PHPT in only one case (2.9%) (Table 2) [1,2,6,24,[26][27][28][29][30][31][32][33][34][35]. This compares with previous reports that 90% of MEN2 patients developed MTC, 50% developed PCC, and 20% to 30% developed PHPT [1,5,6,15].…”
Section: Discussioncontrasting
confidence: 58%
“…The D631Y germline mutation in MEN2 have also been reported in Germany [13,23], the Netherlands [24], and Turkey [25] but they were excluded from this analysis because results of thyroidectomy and family screening were not provided. We found that PCC occurred in 58.8% and MTC in 32.3% of the RET D631Y variant MEN2 patients, and PHPT in only one case (2.9%) (Table 2) [1,2,6,24,[26][27][28][29][30][31][32][33][34][35]. This compares with previous reports that 90% of MEN2 patients developed MTC, 50% developed PCC, and 20% to 30% developed PHPT [1,5,6,15].…”
Section: Discussioncontrasting
confidence: 58%
“…We found 29 cases of MEN2 with metastatic PCC on literature search. The details of these cases, including our two cases, are summarized in Table 2 ( 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…There are six different amino acid substitutions for the same cysteine on codon 634 (F/G/R/S/W/Y), and all of them display comparable transforming activity. The C634Y mutation is believed to confer lower penetrance of the MEN2A phenotype and less aggressive behaviour of MTC than does the C634R mutation 23‐25 . There is higher penetrance of MTC, phaeochromocytoma and hyperparathyroidism in patients harbouring C634R mutation.…”
Section: Discussionmentioning
confidence: 99%